2018
DOI: 10.3390/ijerph15020222
|View full text |Cite
|
Sign up to set email alerts
|

An Online Survey of New Zealand Vapers

Abstract: Using electronic cigarettes (vaping) is controversial, but is increasingly widespread. This paper reports the results of an electronic survey of vapers in New Zealand, a country where the sale and supply of e-liquids containing nicotine is illegal, although vapers can legally access e-liquids from overseas. An on-line survey was conducted, using vaper and smoking cessation networks for recruitment, with follow up surveys conducted 1 and 2 months after the initial survey. 218 participants were recruited. Almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…While ever use of NVPs in our sample was higher (31%) than an online survey of 1001 adults conducted in New South Wales (13%), both studies identified males and current smokers as mostly likely to be NVP users, and smoking cessation as the most common reason for using NVPs . Similar perceived advantages of NVP use were also reported in other studies .…”
Section: Discussionsupporting
confidence: 87%
“…While ever use of NVPs in our sample was higher (31%) than an online survey of 1001 adults conducted in New South Wales (13%), both studies identified males and current smokers as mostly likely to be NVP users, and smoking cessation as the most common reason for using NVPs . Similar perceived advantages of NVP use were also reported in other studies .…”
Section: Discussionsupporting
confidence: 87%
“…An online survey from 2016 provided such information, but was restricted to a small sample of established vapers ( n = 218) recruited mainly through specialist vaping retailers, vaper groups and social media, and hence was unlikely to be representative of all vapers. This survey also included only a small number of people who smoked at the time of the survey ( n = 46), most of whom were occasional smokers, so provided only limited information on vapers who are currently smoking [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…the studied population consisted mainly of men (85.6%) with secondary or higher education (74.8%) living in Poland (98.2%) and definitely speaking in Polish as this was language of the survey. dominance of men in the vapers population is also seen in other studies [21]. in such population, these results may be true, however, they cannot be generalized to the Polish population as a whole.…”
Section: Discussionmentioning
confidence: 51%